Glycosylated 4‐methylumbelliferone as a targeted therapy for hepatocellular carcinoma. (10th December 2021) - Weiz, Gisela; Molejon, Maria I.; Malvicini, Mariana; Sukowati, Caecilia H. C.; Tiribelli, Claudio; Mazzolini, Guillermo; Breccia, Javier D.
Abstract: Background & Aims: Reaching efficacious drug delivery to target cells/tissues represents a major obstacle in the current treatment of solid malignancies including hepatocellular carcinoma (HCC). In this study, we developed a pipeline to selective add complex‐sugars to the aglycone 4‐methylumbelliferone (4MU) to help their bioavailability and tumour cell intake. Methods: The therapeutic efficacy of sugar‐modified rutinosyl‐4‐methylumbelliferone (4MUR) and 4MU were compared in vitro and in an orthotopic HCC model established in fibrotic livers. The mechanistic bases of its selective target to liver tumour cells were evaluated by the interaction with asialoglycoprotein receptor (ASGPR), the mRNA expression of hyaluronan synthases (HAS2 or HAS3) and hyaluronan deposition. Results: 4MUR showed a significant antiproliferative effect on liver tumoural cells as compared to non‐tumoural cells in a dose‐dependent manner. Further analysis showed that 4MUR is incorporated mostly into HCC cells by interaction with ASGPR, a receptor commonly overexpressed in HCC cells. 4MUR‐treatment decreased the levels of HAS2 and HAS3 and the cytoplasmic deposition of hyaluronan. Moreover, 4MUR reduced CFSC‐2G activation, hence reducing the fibrosis. In vivo efficacy showed that 4MUR treatment displayed a greater tumour growth inhibition and increased survival in comparison to 4MU. 4MUR administration was associated with a significant reduction of liver fibrosis without any signs of tissue damage. Further, 60% of 4MUR treated mice did not present macroscopically tumour mass post‐treatment. Conclusion: Our results provide evidence that 4MUR may be used as an effective HCC therapy, without damaging non‐tumoural cells or other organs, most probably due to the specific targeting.